UNVEILING THE MOTIVATIONAL FORCES OF IHSANI SPIRITUALITY: (Implications for Tabligh Assembly of Muhammadiyah in the East Java Region) - Hairul Warizin; Budiyanto Budiyanto; Suwitho Suwitho (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
The research investigates the significance of Ihsani spirituality in enhancing the human resources within the Tabligh Assembly of Muhammadiyah in the East Java region. Its primary objective is to comprehend how Ihsani spirituality serves as a driving force for the tabligh assembly and mubaligh in their efforts to improve human resources. This study aims to contribute to both theoretical understanding and practical application by evaluating the motivational impact of Ihsani spirituality on administrators and instructors within the Tabligh Assembly of Muhammadiyah. Additionally, it seeks to establish Ihsani spirituality as a proposition within the framework of Islamic motivation theory. To achieve these objectives, a qualitative approach is employed, focusing on examining the role of Ihsani spirituality as a motivator for mubaligh within Muhammadiyah in East Java. The research adopts a social constructivism philosophy and utilizes inductive methods such as interviews, observations, and text analysis. Key informants are selected based on their expertise and authority within the Tabligh Assembly. The study highlights the potency of Ihsani spirituality as a motivator for Muhammadiyah mubaligh, emphasizing its focus on the afterlife, Taqwa (piety) towards Allah, goodwill, and sincere acts of charity. The findings of the study ultimately conclude that Ihsani spirituality plays a crucial role in motivating Muhammadiyah mubaligh. By integrating Ihsani values into their daily lives, mubaligh can enhance their capabilities and develop strong principles, thereby contributing to the advancement of Islamic teachings and societal welfare.